The Relationship of the Body-Kinesthetic Intelligence with the Performance of Some Basic Motor Skills among Pre-School Children (5 Years) - Redouane Boubekeur, Benamara Kamel (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The study aims to identify the relationship between body-kinesthetic intelligence with some basic motor skills (running, throwing) among preschool children 5 years. The descriptive approach was retained in the corrective method for its relevance and nature of the study, The descriptive approach was used, while the study sample was selected from of Sonatrach company the children for the academic year 2020/2021, and they numbered 21 children, and they were selected using a simple random method. The results have proved the existence of a significant correlation between the choices of body-kinesthetic intelligence and the results of the motor skill tests. The researcher recommended the need to pay attention to the mental abilities and motor skills abilities of children in the pre-school stage. Keywords: Kinesthetic Intelligence, Motor Skills, Preschool, Children.